Waste Management Performance Towards A Circular Economy In Waste Bank Management System From Maros Regency, Indonesia - Ilham Ilham; Purnomo Yustianto (Government & Resilience, 2024)
Waste management has been in the spotlight in recent years because the amount of waste generated each year is increasing. The circular economy is an economic concept that implements sustainable development goals related to responsible and sustainable levels of consumption and production that can support the community's economy. This study aims to determine performance in understanding waste development and management towards developing an efficient city waste management system that can become a circular economy. The methodology used in this research is an interpretive descriptive qualitative method with a case study approach in Maros Regency, Indonesia, a way of collecting data obtained from various trusted references such as journals, books, etc., this data is then processed by the author. The results of the research show that the performance of the existing waste management system in Maros Regency is running well. The involvement of stakeholders in forming community participation to implement a circular economic system is very helpful because the community can independently improve the economy by managing waste. The Turikale Waste Bank is the central bank. The waste management in Maros Regency is successful because it can provide a turnover of tens of millions per month.